18F-FDG PET/CT-Guided Diagnosis and Evaluation of Treatment Response to Cyclosporine A in Maldistributed Subcutaneous Panniculitis-like T-Cell Lymphoma Without Typical Skin Rash. (February 2020) - Abe, Yoshiaki; Narita, Kentaro; Kobayashi, Hiroki; Kitadate, Akihiro; Takeuchi, Masami; Matsue, Kosei
Abstract : Abstract: A 30-year-old woman presented with persistent fever and elevated lactate dehydrogenase levels without skin rash. 18 F-FDG PET/CT revealed FDG uptake in subcutaneous tissues in the forearm, buttocks, and lower limbs, whereas the trunk was unaffected. She was diagnosed with subcutaneous panniculitis-like T-cell lymphoma based on a PET/CT-guided subcutaneous tissue biopsy from the thigh. Although conventional cytotoxic agent–based chemotherapies failed to achieve disease remission, subsequent cyclosporine A treatment promptly resolved the fever and laboratory abnormalities. Remarkably, abnormal FDG uptake disappeared entirely on follow-up PET/CT, demonstrating its utility in the evaluations of responses to emerging cyclosporine A–based treatments in subcutaneous panniculitis-like T-cell lymphoma.